2019
DOI: 10.3329/jbau.v17i3.43197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydropriming on seed germination, seedling growth and yield of bitter gourd

Abstract: The experiment was conducted to find out the effects of hydropriming on seed germination, seedling growth and yield of bitter. Two single factor experiments were conduced at the laboratory and field of Seed Science and Technology Department following completely randomized design with three replications and randomized complete block design with five replications, rspectively. The experiments comprised six soaking treatments viz. T0: untreated (control), T1: tap water (around 25º ± 2º C) for overnight, T2:cold w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
4
14
0
Order By: Relevance
“…The seedling vigor index is growing due to reduced imbibition lag time for priming treatments [ 44 ]. Similar results were reported during the study of germination and field performance of vegetables; faba bean [ 45 ], bitter gourd [ 27 ], cucumber [ 37 ], and food crops [ 30 , 46 ]. Priming often induces physiological and biochemical seed modifications during seed treatments [ 47 ] and increased amylase production enhances metabolic tasks, resulting in higher seed vigor [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The seedling vigor index is growing due to reduced imbibition lag time for priming treatments [ 44 ]. Similar results were reported during the study of germination and field performance of vegetables; faba bean [ 45 ], bitter gourd [ 27 ], cucumber [ 37 ], and food crops [ 30 , 46 ]. Priming often induces physiological and biochemical seed modifications during seed treatments [ 47 ] and increased amylase production enhances metabolic tasks, resulting in higher seed vigor [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
“…Hydro-priming is an economic and eco-friendly technique [ 26 ] that is done by soaking seeds either in hot or in cold water for a certain period before sowing seeds in the field or any growing/nutrient media [ 27 ]. This facilitates water imbibition in seed and makes seed coat soft enough for enhanced easy and fast growth of seed embryo [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…But, the highest value of mean germination time was recorded by seed soaking in boiled water for 60mintes. The results partially similar to those obtained by Farajollahi et al, (2014) concerning Calotropis persica plant, Tania et al, (2019) concerning Momordica charantia L. plant and Usman et al, (2010) concerning Acacia senegal plant.…”
Section: -Lath House Experimentssupporting
confidence: 89%
“…In addition, water also causes the embryonic cell wall and seed coat more permeable to gases, thus facilitates the diffusion of oxygen into the cells to increase the respiratory activity of the embryonic cells so that the process of seed germination occurs faster (Taiz & Zeiger, 1998). According to Tania et al (2019), seed priming treatment can stimulate a series of biochemical changes in the seeds to initiate important processes such as breaking dormancy and hydrolysis.…”
Section: Effect Of Seeds Hydropriming On Embryo Germinationmentioning
confidence: 99%
“…Other study reported by Shah et al (2012) said that seed priming increased early growth and seedling vigor of mung bean, characterized by an increase in seedling biomass. Bitter gourd seeds soaked in 45°C warm water for 5 min can also increase seedling growth and yields (Tania et al, 2019).…”
Section: Plantlet Regeneration From Germinating Embryosmentioning
confidence: 99%